Diagnostic Value and the Role of Inferior Vena Cava DiameterCollapsibility Index to Evaluate Dry Weight in HemodialysisPatients - Yussac, Muhammad Artisto Adi; Dharmeizar, Dharmeizar; Abdullah, Murdani; Antono, Dono; Muhadi, Muhadi (Jurnal Penyakit Dalam Indonesia, 2016)
Introduction. In daily clinical practice, fluid status in Hemodialysis (HD) patients is well correlated with dry weight calculation. Dry weight calculation is commonly practiced by clinical observation, which is not accurate. Because of these, few methods has been suggested to calculate the dry weight non-invasively. Bioelectrical Impedance Analysis (BIA) is widely available in overseas but not readily available in all dialysis center in Indonesia, while inferior vena cava diameter is a relatively inexpensive method, and readily available in all dialysis center because it can be performed with ultrasonography (USG) instrument. Methods. A cross-sectional study was performed in a group of regular HD patients at the Haemodialysis Unit, Cipto Mangunkusumo Hospital in Jakarta, June 2011. Dry weight was evaluated with bioelectrical impedance analysis, while the inferior vena cava collapsibility index was evaluated using USG performed by two different observer. Results. We have recruited 30 HD patients, in which 18 (60%) of the subjects were overload according to the bioelectrical impedance analysis, while 21 (70%) were overload according to the inferior vena cava collapsibility index. The mean age of the subjects is 52 years old with the minimum 24 and maximum 69 years. In this research, we found negative correlation (r = -0.957, P<0.0001) between inferior vena cava colapsibility index and BIA. We found a 94.4% sensitivity and 66.7% specificity for inferior vena cava colapsibility index. Both of USG operators showed a κ coefficient value of 0.92, which reflected a very strong agreement between them. Conclusions. The inferior vena cava colapsibility index have a good role as a screening method in determining dry weight in dialysis patients